Brain imaging in patients with transient ischemic attack: a comparison of computed tomography and magnetic resonance imaging - Förster, Alex; Gass, Achim; Kern, Rolf; Chatzikonstantinou, Anastasios; Hennerici, Michael G.; Szabo, Kristina (European neurology, 2012)
Background: Brain imaging in stroke aims at the detection of the relevant ischemic tissue pathology. Cranial computed tomography (CT) is frequently used in patients with transient ischemic attack (TIA) but no data is available on how it directly compares to magnetic resonance imaging (MRI). Methods: We compared detection of acute ischemic lesions on CT and MRI in 215 consecutive TIA patients who underwent brain imaging with either CT (n = 161) or MRI (n = 54). An MRI was performed within 24 h in all patients who had CT initially. Results: An initial assessment with CT revealed no acute pathology in 154 (95.7%) and possible acute infarction in 7 (4.3%) patients. The acute infarct on CT was confirmed by diffusion-weighted imaging (DWI) in only 2 cases (28.6%). DWI detected an acute infarct in 50 of the 154 patients with normal baseline CT (32.5%). Among 54 patients without baseline CT, DWI showed acute ischemic lesions in 19 (35.2%). The ischemic lesions had a median volume of 0.87 cm3 (range: 0.08-15.61), and the lesion pattern provided clues to the underlying etiology in 13.7%. Conclusion: Acute MRI is advantageous over CT to confirm the probable ischemic nature and to identify the etiology in TIA patients.
Gesehen am 10.04.2018